Anion–π Interaction‐Induced Room‐Temperature Phosphorescence of a Polyoxometalate‐Based Charge‐Transfer Hybrid Material. Issue 41 (19th June 2018) - Liao, Jian‐Zhen; Meng, Lingyi; Jia, Ji‐Hui; Liang, Dong; Chen, Xu‐Lin; Yu, Rong‐Min; Kuang, Xiao‐Fei; Lu, Can‐Zhong
Abstract: Room‐temperature phosphorescence (RTP) was realized for the first time in a polyoxometalate‐based charge‐transfer (CT) hybrid material bearing polyoxometalates (POMs) as electron‐donors (D) and rigid naphthalene diimides (NDIs) as electron‐acceptors (A), meanwhile, this hybrid material displayed photochromism as well. The significant D‐A anion–π interaction induced an additional through‐space charge‐transfer pathway. The resulting suitable D‐A CT states can efficiently bridge the relatively large energy gap between the NDI‐localized 1 π–π* and 3 π–π* states and thus trigger the ligand‐localized phosphorescence ( 3 π–π*). Abstract : A unique polyoxometalate‐based charge‐transfer complex displays both photochromism and room‐temperature phosphorescence in ambient conditions, which are mainly attributable to the charge transfer behaviors induced by unorthodox anion–π interactions. The strategy of introducing intermolecular charge‐transfer states may open up new opportunities for developing efficient organic–inorganic hybrid photofunctional materials.